Pelatihan Penggunaan Sistem Informasi Pengelolaan Surat Keluar di Desa Dunggala Kecamatan Tapa Kabupaten Bone Bolango - Wrastawa Ridwan; Rahmat D. R Dako (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Assessment of good government performance is characterized by the quality of its services to the community. One of the roles of the village as the lowest administrative level in a region is to serve the community in making letters. Management of outgoing mail in Desa Dunggala, Kecamatan Tapa, Kabupaten Bone Bolango is still done conventionally, namely by recording the letter number in the agenda book. This resulted in village officials experiencing difficulties in managing the correspondence archives if in the future a letter with a certain number was needed. This community service activities aimed at helping the village government in managing outgoing mail by designing information system for managing outgoing mail. The information system was built based on the web application, but in its application is still used offline or localhost, due to internet network constraints in the village office. A database system is used for data storage so that it is easy to search the letters that have been made. Then, the village officials has been trained to use the information system. The results obtained from this activity are the information system for managing outgoing mail and the training of village officials in using the application. This information system can be further developed by taking into account the needs that exist in the village.